Private Business’ Roles as Stakeholders in Developing Surabaya as Tourism Destination - Agoes Tinus Lis Indrianto; Kadir H. Din; Basri Rashid (Journal of Indonesian Tourism and Development Studies, 2017)
According to UNWTO report, the international tourist arrivals reached 1.2 billion people in 2016. There was 5% growth in the developed countries and 2% growth in the developing countries, including Indonesia. In 2016, Indonesia welcomed 11.52 million international tourists. As the second biggest city in Indonesia, Surabaya has important roles for the country. Receiving around 564,000 international tourists in 2016, Surabaya had changed into a tourism destination. The development began in 2005 when Surabaya Tourism Promotion Board was set up to promote the city tourism. This board consists of private tourism business, such as hotels, restaurants, travel agents and tourist attraction operators. They are working together with other tourism stakeholders in Surabaya. This study aims to reveal the roles of private business in developing Surabaya as tourism destination. The study describes the activities done by private business to develop Surabaya, such as conducting promotional activities, developing products, initiating new programs and joining in international events. Moreover, they are actually helping their own business as well as supporting tourism destination development in Surabaya. This study shows that commitment, consistency, and collaboration among private business as the stakeholders are the keys to develop tourism destination in Surabaya.Keywords: Destination, Development, Private Business, Roles, Surabaya, Tourism.